Prevalence of smokeless tobacco use in India and its association with various occupations: A LASI study - Bharati, Bhavna; Sahu, Kirti Sundar; Pati, Sanghamitra (Frontiers in Public Health, 2023)
Background: More than two-thirds of death in developing countries are due to non-communicable diseases, and tobacco is a leading risk factor. Among different socio-demographic factors, different types of occupation have an impact on the use of smokeless tobacco. The objectives of this study are to find out the overall prevalence of smokeless tobacco use ever and current use), the pattern of association with various occupations and related variables (current and past workers) and the role of childhood adversity on the initiation and use. Methods: This study used data from Longitudinal Ageing Study in India (LASI) wave 1, a Nationally representative cross-sectional study collected in 2017-18. Current and ever users of smokeless tobacco are taken into consideration as the target population. For the data analysis, survey-weighted tools have been applied for descriptive statistics and multivariable logistic regression model. The weighted data analysis has been done using R studio with R version 4. Results and Discussion: From the sample size of 65561, 38% have ever used either smoking or smokeless tobacco. Among them, 40 % use tobacco in smoke form, 51 % use smokeless tobacco, and 9 % take both. At the population level, 22.8% and 20.4% are ever and current users of smokeless tobacco, respectively. Type of occupation, type of employer, place of work, kind of business, and workload in the occupation was found to be significantly associated with smokeless tobacco use. A deaddiction and tobacco quitting policy targeting rural male informal workers should be the focus of the Government.